0534 Dysphagia Severity is Associated with Worse Sleep Disordered Breathing in Infants with Trisomy 21. (25th May 2022) - Cho, Yeilim; DelRosso, Lourdes; Sobremonte-King, Michelle
Abstract: Introduction: Hypotonia is common in infants with Trisomy 21. This can cause masticatory and oropharyngeal muscle weakness increasing the risk for dysphagia and sleep disordered breathing. Data describing the occurrence of dysphagia and sleep disordered breathing in infants with Trisomy 21 is limited. This study aims to determine the frequency and severity of dysphagia and its relationship to polysomnogram parameters in infants with Trisomy 21. Methods: Retrospective chart review of patients with Trisomy 21 <12 months old that underwent polysomnography at Seattle Children's Hospital between October 1, 2015-August 23, 2021. Data collected included: sex, age, presence of dysphagia, recommended thickener type and polysomnographic data. Results: A total of 526 polysomnograms in patients with Trisomy 21 were performed. Forty-one studies were identified in <12 months old. Results in mean ± SD showed: age 6.5 months + 3, 66% were male and 73% were diagnosed with dysphagia through a video fluoroscopic swallow study. In those with dysphagia, 16% can tolerate thin liquids, 20% prescribed nectar-thick, 7% prescribed honey-thick and 57% were G-tube dependent. In patients with dysphagia compared to those without dysphagia: there was higher total AHI of 43.3 +/- 35.3 vs. 22.6 +/- 10.6 (p=0.006), oAHI of 39.7 +/- 35.5 vs. 17.2 +/- 11.6 (p=0.004), CAI of 3.4 +/- 3.4 vs. 3.4 +/- 1.8 (p=0.11), oxygen saturation nadir of 78.6 +/- 10.6 vs. 83.1 +/- 6.6 (p=0.11) and percentage total sleep time TcCO2 >50 mmHg of 44.6 +/- 42.6 vs. 31 +/- 40.3 (p=0.44). Worse dysphagia was positively correlated with a higher oAHI (r=0.38, p=0.03). Conclusion: There is a high incidence of dysphagia and sleep disordered breathing in infants with Trisomy 21. Dysphagia severity correlated with oAHI severity. Dysphagia in OSA can be due to the sensory and motor changes of the pharynx with impaired swallow-breathing mechanism. Chronic microaspiration can also result in decreased pulmonary reserve from lower airway inflammation or lung parenchymal disease, which may lead to worse sleep disordered breathing. Current guidelines suggest screening at school age or when there are clinical symptoms of OSA in Trisomy 21. However, results suggest the need to evaluate and intervene earlier especially in infants with dysphagia. Support (If Any):